Analisis Naratif Penerapan Pengambilan Keputusan Finansial pada UMKM (Kopi Limantan) - Dali, Meilina Widya; Panigoro, Rafianda Dyah Pricilia; Antule, Nur Ain; Lolong, Brigitha Aurelia; Mohamad, Afrilyansyah Zumria; Zakaria, Celsi Olifia M.; Bumulo, Nurul Pratiwi; Lestari, Diah Ayu; Ain, Nur; Bela, Mega Shintya; Atima, Sri Nanda; Podungge, Selpiyanti; Darise, Cahaya Ramadhani; Kasim, Nurhalima (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study investigates the business resilience tactics and financial decisions of the Kopi Limantan MSME located in Gorontalo. Using qualitative methods and a narrative analysis design, this research examines the business's journey from managerial failure at its previous branch to successful reconsolidation with an adaptable cart business model since 2024. Data collection was conducted through in-depth interviews, observations, and document review, involving the business owner as the key informant. The results of this study indicate that Kopi Limantan is able to create a competitive advantage through a specific "market algorithm" strategy, targeting products at the women and children segment and diversifying revenue into the banking sector (B2B). Operationally, the implementation of a cost-of-sale (COGS)-based management system and the use of a percentage wage system have proven effective in maintaining financial stability. The study concludes that Kopi Limantan's sustainability relies heavily on a combination of friendly personal service and disciplined adherence to proven operational standards. These findings emphasize the importance of flexibility in the business model and an understanding of local demographics to address changes in the coffee industry at the regional level.